Specificities of Approaches to Anticoagulant Therapy in Comorbid Patients with Atrial Fibrillation, Diabetes Mellitus and Impaired Kidney Function - N. V. Drobotya; E. Sh. Guseynova; A. A. Pirozhenko (Столичная издательская компания, 2020)
Comorbid patients with atrial fibrillation, diabetes mellitus and chronic kidney disease are at high risk of stroke. The direct oral anticoagulants are indicated for them. The choice of a drug should be based on the results of randomized clinical trials, in which the patients profile corresponds to that in the real Russian clinical practice as much as possible. Taking into account the peculiarities of comorbidity in this category of patients, the requirements for their protection should be considered comprehensively. Along with the prevention of thromboembolic complications, it is necessary that the selected direct oral anticoagulant provides a reduction in the risk of cardiovascular complications, which are typical of diabetes mellitus, and slows down the progression of renal filtration function decline. Rivaroxaban may meet these requirements; its use has significant advantage in high adherence to therapy.